Defective IgG2 response to Pneumovax in HIV seropositive patients. Issue 5 (October 1993) - Unsworth, D J; Rowen, D; Carne, C; Sonnex, C; Baglin, T; Brown, D L
Abstract : OBJECTIVE–To determine whether HIV (Human Immunodeficiency Virus) antibody positive adults are capable of mounting an effective immune response when immunized with polyvalent pneumococcal vaccine. DESIGN–28 patients (nine homosexual men, one bisexual man, three heterosexual females, 10 injecting drug abusers, five haemophiliacs) and 11 healthy volunteers, were immunised with Pneumovax II and titres of IgG1 and IgG2 specific antibody measured before and 1 month after immunisation. Magnitude of immune response was related to CD4 T-lymphocyte count at time of immunisation to establish whether responses are better in early disease. MAIN OUTCOME MEASURES–Based on our data in healthy volunteers we defined an adequate response to Pneumovax II as a post immunisation IgG2 antibody level at least 50% greater than the pre immunisation level. RESULTS–The magnitude of the response was significantly higher in the normal volunteers (U = 95; p = 0.0328). Adequate IgG2 responses were seen in 11/11 normals but in only 14/28 HIV seropositives (chi 2 = 8.58; p < 0.01). Poor responses were unrelated to the CD4 T-lymphocyte count at immunisation. Absolute IgG2 deficiency accounted for the poor response in only 1 HIV patient. CONCLUSION–50% of HIV antibody seropositive individuals fail to mount adequate immune responses to polyvalent pneumococcal vaccine. Non responders are unlikely to be protected.